Care needs of women in climacteric with hypertension: nurses' work possibilities - Lara Castilhos; Maria Denise Schimith; Laís Mara Caetano da Silva; Lisie Alende Prates; Nara Marilene Oliveira Girardon-Perlini (Universidade Federal de Santa Maria, 2021)
Objective: To understand the care needs of women in climacteric with Systemic Arterial Hypertension (SAH). Method: this is qualitative research developed in 21 Family Health Units (FHUs), during April and June 2019. Fifteen women between 40 and 69 years old participated; with a referred diagnosis of SAH, attached to the FHUs and who reported not using hormonal contraceptives. We used semi-structured interviews, followed by the construction and return of narratives, with participatory analysis. Results: care needs included management of signs and symptoms; monitoring blood pressure levels, effectiveness, and treatment adherence; guidance on food choices; search for reliable information, and active listening. The perception of the nurse's work referred to individual and punctual care. Conclusion: the climacteric is experienced differently and the needs of women show different possibilities for improving care. This identification allows the nurse to develop individualized care and adapted to the demands of women.